Moisture and temperature influence on mechanical behavior of PPS/buckypapers carbon fiber laminates - Rojas, J. A. [UNESP]; Santos, L. F.P. [UNESP]; Costa, M. L. [UNESP]; Ribeiro, B. [UNESP]; Botelho, E. C. [UNESP] (IOP Publishing, 2017)
In this work, multiwall carbon nanotubes (MWCNT) were dispersed in water with the assistance of water based surfactant and then sonicated in order to obtain a very well dispersed solution. The suspension was filtrate under vaccum conditions, generating a thin film called buckypapers (BP). Poly (phenylene sulphide) (PPS) reinforced carbon fiber (CF) and PPS reinforced CF/BP composites were manufactured through hot compression molding technique. Subsequently the samples were exposed to extreme humidity (90% of moisture) combined with high temperature (80 °C). The mechanical properties of the laminates were evaluated by dynamic mechanical analysis, compression shear test, interlaminar shear strength and impulse excitation of vibration. Volume fraction of pores were 10.93% for PPS/CF and 16.18% for PPS/BP/CF, indicating that the hot compression molding parameters employed in this investigation (1.4 MPa, 5 min and 330 °C) affected both the consolidation quality of the composites and the mechanical properties of the final laminates.
Keywords: Carbon fiber; Carbon nanotube buckypaper; Mechanical properties; Poly phenylene sulphide